The Development of Sustainable Business Models: Concept, Elements and Importance - Olusola-Christwealth, Delightsome; Kiaušienė, Ilona (Vilnius University Proceedings, 2023)
Advances in technology, falling trade barriers, economies of scale and domestic market saturation are considered some of the key drivers behind globalisation. Globalising businesses require the management of complex solutions to coordinate resources and processes across functions and geographies. The importance of strong business models is therefore vital in view of increasing global competition. Aided by the development of sustainable business models, entrepreneurs and small firms can confidently participate in networks and capture value from networking relationships, regionally and internationally, to enhance their global presence. The aim of this research is to investigate the importance of development of sustainable business models for international companies. Results showed the development of sustainable business models are important in motivating corporate innovative measures for sustainability, and this is a driving force behind competitiveness